Preliminary study on the avifauna of the Van Ban proposed natural reserve, Lao Cai province - Hung, Le Manh (Academia Journal of Biology, 2015)
A total of 156 bird species belonging to 10 orders, 34 families were recorded in Vanban district, Laocai province. Among them, two species are listed in the Threatened Bird of Asia [2,4] as globally vulnerable or near threatened: beautiful nuthatch, yellow-billed nuthatch; three species are listed in the List of Threatened Species (IUCN 1996); three species are listed in the Red Data Book of Vietnam [3]. Furthermore, the Vanban district supports two restricted-range species that define the Fansipan, Hoang Lien mountains and Northern Laos Secondary EBA: yellow-billed nuthatch, long-billed wren babbler [7]. There are five new species and 11 new range extension species following the Checklist of the Bird of Vietnam (Vo Quy, Nguyen Cu), [9]; 14 new altitude extension and 2 new range extension species following the Robson [6]. There are also 15 species restricted to the Sino-Himalayan temperate forest biome, 40 species restricted to the Sino-Himalayan subtropical forest biome and 6 species restricted to the Indochinese tropical moist forest biome.